Perancangan Sistem Pelayanan Informasi Berbasis Android dengan Algoritma Nazief Andriani (Studi Kasus : Universitas Katolik Santo Thomas) - Ita Juwita Saragih; Zakarias Situmorang (JUKI : Jurnal Komputer dan Informatika, 2019)
Service is an effort to help prepare what others need. Or it can be interpreted that service is a series of activities or processes that fulfill the needs of others more satisfactorily. To simplify the services available at the Catholic University of Santo Thomas, it is necessary to build an android-based information service system with Nazief Andriani algorithm. This algorithm is able to find the basic words of each input so that it can produce a separate output or in other words the output issued right on target or on purpose. With this system, students no longer need to come to the administrative unit or via chat to get information about activities or complaints that are received or what they want to convey. So that this system is expected to make it easier for users to get accurate, efficient information and does not require a relatively long time, causing slow, limited and unresponsive service in providing answers.